Management and fire, a critical combination for Eucalyptus globulus dispersal - Anjos, Andreia (2021)
In a context of growing demands for wood and wood derived products, plantations of exotic tree species have globally increased. Fast growth and high productivity made Eucalyptus one of the most successful tree genus around the world. Nevertheless, this genus is often associated with negative ecological impacts on biodiversity and ecosystem functioning and the risk of expansion is considered a major threat. Eucalyptus globulus is the most planted tree species in Portugal, but common silvicultural measures, including periodic control of the understory vegetation, have traditionally limited natural regeneration. However, forest fires constitute a main driver of E. globulus dispersal and regeneration and, under the current climatic change scenario, the possible extension of the summer fire regime to previous months in spring and/or later months in autumn, may have a profound effect on E. globulus dispersal capacity. Moreover, isolated eucalypt trees, seed-trees, are often left uncut and many plantations are poorly managed potentially increasing the risk of E. globulus dispersal. To evaluate the impact of both management and fire event dates on E. globulus dispersal, we assessed the establishment of saplings beyond plantations and seed-trees surrounding areas in absence of fire and after 2017 June and October fires in managed and unmanaged conditions. Sapling survival was also analyzed two years after fire. Our results point out that sapling establishment in our study area is not a major concern in the absence of fire. Also, our findings showed that E. globulus establishment is highly dependent on the time of the year a fire occurs and that pre-fire management practices constrain E. globulus dispersal. We also found that seed-trees are high seed dispersers after fire even in managed conditions, deserving great concern. Additionally, sapling survival two years after October fire indicate that out of season fires might constitute an emerging issue regarding E. globulus expansion.